(3cfR GdCSQGQ hdhGbM GdCacGQs - (3GdUfgGLj , CHh YHO Gddg eMeO Hf SYjO Hf YeQ Hf SYjO GdUfgGLj, GHf eTGHP,J (B795 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhgGH GdaJGM , GdefYe GdQMef , aGdb GdEUHGM hdeG cGf GdfXQ hGdEYJHGQ ai eG CHOYJg GdbOQI GdEdgjI ef CLfGS GdehLhOGJ hCfhGY GdeNdhbGJ SHHkG dMUhd GdeYGQa hSejJg s
(3BNQgG (B:s
(3hbO EfYbO ELeGY Cgd GdSfI Ydi Pdc NdGakG dCHi GdgPjd GdeYJRdi hGddg GdeSJYGf Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3Ydi WQJgG JedcGJ efgG Jedc HGSe eMeO Hf eMeO Hf ESeGYjd Hf YHO GdQMef Hf ESeGYjd Hf eWgQ Hf ESeGYjd Hf jMji Hf GdMSjf Hf GdbGSe Hf eMeO s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdESdGejs